Design Analysis of a Tubular Chassis for an Electric Vehicle using Finite Element Method - Nanang Ali Sutisna (President University, 2023)
In these new eras, human race was stuck between fully converting vehicles using an electric motor or combustion engine. It is a known fact that people were forced by the government to reduce carbon footprint, with the new regulation of Carbon tax that will be implemented in 2022 by the government. The main purpose of this research is to design a chassis for an electric vehicle with a Torsional Bar front suspension and single rear shock breaker is to help reducing carbon production in the future. By developing a chassis for an electric Go-Kart, the students of President University is one step closer to develop an electric vehicle that can be used by everyone and become a leading green technology innovator in Indonesia, this research will test the capability of the chassis to endure certain loads with a few limitations, the 3D design will be performed in software called Solidworks while the static structural, modal analysis, and Harmonic Response Simulation will be performed in Ansys using the finite element method. The expected results from this research is a sufficient design of electric go-kart through a stress analysis, safety factor analysis, chassis deflection analysis, and chassis natural frequency analysis.